Effect of age on serum metabolites of female Brahman crossbred cattle raised in an integration system of cattle-oil palm plantation in Central Kalimantan - Kristanto, D.; Widiyono, I. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
The study was aimed to evaluate the effect of age on the serum metabolite of female Brahman crossbred cattle raised extensively under the cattle-oil palm integrated system for 3 months. Thirty calves aged 3-6 months, 30 heifers aged 12-18 months, and 30 cows aged 48 months which were clinically healthy were selected and used in this study. Blood samples were collected from coccygeal vein. The serum was separated by centrifugation and stored at -20oC until the time of analysis. Blood samples were collected from coccygeal vein as much as 4 mL. Serum metabolites were determined using an autoanalyzer (The Roche/Hitachi Cobas 6000 analyzer). Serum concentration of ALB, Ca, P, Na, K, and Cl in calves were higher than heifers and cows (P<0.05), while serum creatinine, total protein, blood urea nitrogen (BUN) and globulin concentration in cows were higher than those ofcalves (P<0.05). Serum glucose concentration in calves and heifer was higher than that in cows (P<0.05). It could be concluded that the age factor must be considered in the interpretation of the results of the examination of the serum metabolites of Brahman crossbred cattle raised extensively in oil palm plantations.